Letter from the ship Navigator - Navigator (Ship)
Anonymous letter (1847 March 6; Callao, Peru) written aboard the ship Navigator of Nantucket, Mass., George Palmer, master, addressed to the writer's mother, Deborah P. Chase. Notes amount of oil aboard, a visit to Pitcairn Island, the presence of the ship Young Hero of Nantucket, William B. Swain, master, at Callao, and a fire in Nantucket in July 1846.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chase, Deborah P. -- Correspondence; Palmer, George -- (Whaling master); Swain, William B; Young Hero (Ship); Fires -- Massachusetts -- Nantucket; Whaling -- Massachusetts -- Nantucket; Whaling -- Pacific Ocean; Whaling -- Peru -- Callao; Callao (Callao, Peru) -- Description and travel; Pitcairn Island -- Description and travel